Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah pada PT Bank BTN Cabang Panakkukang Kota Makassar: Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah - Adryan Adryan; Aulia Aulia; Sherry Adelia Natsir Kalla (Politeknik Negeri Jakarta, 2025)
This research aims to analyze the influence of service quality on customer satisfaction at PT Bank BTN Panakkukang Branch, Makassar City. Data was collected through questionnaires distributed to 120 respondents. Data analysis was carried out using the Statistical Package for the Social Sciences.SPSS version 29 software, with a simple linear regression method to identify the relationship between service quality variables and consumer satisfaction. The results of descriptive analysis show that the average service quality score is 4.12, and consumer satisfaction is 4.16. Simple regression analysis shows that these variables simultaneously have a significant effect on consumer satisfaction (F=215.328; p<0.05F= 215.328; p<0.05. Partially, the service quality variable has an influence coefficient of 0.809 Keywords: Service quality, customer satisfaction